2001
DOI: 10.1038/oby.2001.59
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Levels Are Associated with Fat Oxidation and Dietary‐Induced Weight Loss in Obesity

Abstract: Objective: To examine the relationship between fasting plasma leptin and 24-hour energy expenditure (EE), substrate oxidation, and spontaneous physical activity (SPA) in obese subjects before and after a major weight reduction compared with normal weight controls. To test fasting plasma leptin, substrate oxidations, and SPA as predictive markers of success during a standardized weight loss intervention. Research Methods and Procedures: Twenty-one nondiabetic obese (body mass index: 33.9 to 43.8 kg/m 2 ) and 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
2
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 57 publications
8
48
2
1
Order By: Relevance
“…Verdich also showed that leptin was inversely related to weight loss in 28-39-year old men, indicating that an increase in leptin sensitivity was associated with greater weight loss. 30 Moreover, in a prospective analysis of the Health Professionals Follow-Up Study of overweight men, weight gain over 4 years was associated with a high leptin level. 53 In conclusion, the weight loss intervention utilized in this study produced significant changes in body weight and in leptin concentrations at the 6-and 18-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Verdich also showed that leptin was inversely related to weight loss in 28-39-year old men, indicating that an increase in leptin sensitivity was associated with greater weight loss. 30 Moreover, in a prospective analysis of the Health Professionals Follow-Up Study of overweight men, weight gain over 4 years was associated with a high leptin level. 53 In conclusion, the weight loss intervention utilized in this study produced significant changes in body weight and in leptin concentrations at the 6-and 18-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…40 These studies demonstrate that leptin is involved in the regulation of body energy balance. 30,41 Recent evidence hints that leptin may be involved in certain disease states. Levels of this hormone are elevated in synovial Leptin, weight loss, and exercise GD Miller et al fluid in patients with OA compared to normal controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As fa/fa rats lack the leptin receptor and leptin stimulates skeletal muscle fat oxidation (26,27), the reduced fat oxidative capacity at early age in fa/fa rats might be due to the ablation of the leptin receptor. This makes this model suitable to investigate the consequence of reduced fat oxidation on the development of type 2 diabetes.…”
Section: Articles Integrative Physiologymentioning
confidence: 99%